2016
DOI: 10.1016/j.yjmcc.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel NaV1.5 voltage sensor mutation associated with severe atrial and ventricular arrhythmias

Abstract: Background Inherited autosomal dominant mutations in cardiac sodium channels (NaV1.5) cause various arrhythmias, such as long QT syndrome and Brugada syndrome. Although dozens of mutations throughout the protein have been reported, there are few reported mutations within a voltage sensor S4 transmembrane segment and few that are homozygous. Here we report analysis of a novel lidocaine-sensitive recessive mutation, p.R1309H, in the NaV1.5 DIII/S4 voltage sensor in a patient with a complex arrhythmia syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
4
17
0
1
Order By: Relevance
“…Those results were basically consistent with previous studies (16,17). As for R965C-R1309H mutations, compared to R1309H mutation, it induced more significant depolarization shift of activation curve, V 1/2 and slope factor, suggesting that Na v 1.5 R965C-R1309H channel was activated at the much more depolarized membrane potential and displayed slower activation (Supplement 3).…”
Section: Electrophysiological Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…Those results were basically consistent with previous studies (16,17). As for R965C-R1309H mutations, compared to R1309H mutation, it induced more significant depolarization shift of activation curve, V 1/2 and slope factor, suggesting that Na v 1.5 R965C-R1309H channel was activated at the much more depolarized membrane potential and displayed slower activation (Supplement 3).…”
Section: Electrophysiological Characteristicssupporting
confidence: 92%
“…Consistent with previous literatures reported (16,17), as shown in the Figure 4A-C and Table 2, the R1309H mutation, but not R965C mutation, significantly reduced the Na + current density at a series of test potentials ranging from -45 mV to -15 mV when compared to the WT group (Supplement 1). More importantly, we found that R965C-R1309H mutations resulted in a more severe reduction in Na + current density ranging from -45 mV to 30 mV compared to the WT group.…”
Section: Electrophysiological Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…Ion channels represent a family of important membrane proteins that conduct ions across the membrane, thereby controlling the intracellular ion content, membrane potential and action potentials. The abnormal function and structure of ion channels can lead to a variety of cardiovascular diseases (Ackerman, ; Navedo et al, ; Hsiao et al, ; George, ; Wang et al, ). More importantly, endogenous sulfur‐containing gaseous signal molecules play an important role in the pathogenesis of cardiovascular diseases by targeting ion channels (Wang, ; Brampton and Aaronson, ).…”
Section: Introductionmentioning
confidence: 99%